Pendidikan karakter: Tantangan, peluang dan implementasi - Azkiya, Muhammad Fadzlulloh (Maliki Interdisciplinary Journal, 2024)
Character education is an important aspect in forming a young generation with noble character and noble character. This research aims to identify various challenges and opportunities in the implementation of character education in Indonesia, analyze the factors that influence the success of its implementation, and formulate recommendations to strengthen its implementation. The research method used is a literature study with a qualitative approach. Research data was collected from various literature sources, such as scientific journals, books, scientific articles and research reports. The research results show that there are various challenges in implementing character education in Indonesia, such as a lack of comprehensive understanding, not yet optimal integration in curriculum and learning, limited resources, lack of synergy between parties, and changing community culture and values. Even though there are various challenges, there are also several opportunities that can be optimized to strengthen the implementation of character education, such as strong government commitment, increasing public awareness, developments in information and communication technology, the potential for collaboration between parties, and cultural diversity and local values. Based on the results research, several strategies are recommended to strengthen the implementation of character education in Indonesia, such as increasing the capacity of educators and education personnel, developing curriculum and character learning, etc.